Evaluation of open source systems for managing business rules in enterprise scenarios - Pacheco-Cárdenas, Yoan; Rodríguez-Rodríguez, Ernesto; González-González, Luisa (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
In this work are investigated open source systems that manage business rules in two different enterprise scenarios taking into account technological properties of the tool and cultural properties of the environment in the enterprise. Drools get the highest score in all two scenarios and release its greatest potential when editing rules is the responsibility of the IT team. OpenRules and OpenL Tablets reach the second and third places in all scenarios. Both programs get the best results when editing rules is the responsibility of business experts and the quantity of complex rules is not high. This research help to select which business rules management system should be connected with enterprise applications of a company that follows the business rules approach to develop computer systems.